A conceptual process model to improve voter participation in Nigeria election. (26th August 2021) - Simon, Ashiru; Dams, Gabriel Lazarus; Danjuma, Salome
Insecurity at every polling unit is one of the major reasons why the number of voters participating in Nigerian elections is continuously on the decrease. In the 2011 presidential election for instance, the number of people killed was estimated to be between 800 and 1, 000. More so, statistics has it that voters' turnout for the presidential elections in 2007, 2011 and 2015 was 58%, 53.68% and 43.65% respectively showing a progressive decrease. In this paper, a process model for the existing election system currently used in Nigeria is designed to capture the voting system. The designed process model is modified by embedding an existing technology known as unstructured supplementary service data (USSD). A prototype is developed for demonstration. The adoption and deployment of the prototype will encourage eligible voters' turnout and minimise the degree of rigging, human labour, loss of lives and the overall voting time.